2022
DOI: 10.3390/d14070576
|View full text |Cite
|
Sign up to set email alerts
|

The Biodiversity of Calcaxonian Octocorals from the Irish Continental Slope Inferred from Multilocus Mitochondrial Barcoding

Abstract: Deep-sea corals are important benthic inhabitants that support the biodiversity and function of the wider faunal community; however, their taxonomy is underdeveloped and their accurate identification is often difficult. In our study, we investigated the utility of a superextended (>3000 bp) barcode and explored the effectiveness of various molecular species delimitation techniques with an aim to put upper and lower bounds on the estimated number of calcaxonian species in Irish waters. We collected 112 calca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…These 121 individuals span 11 of 12 previously defined groups, with only G1 absent from our analyses. Previous phylogenies (mtMutS-5′, mtMutS-3′, and 18S in Watling et al, 2022; mtMutS-5′, 16S, and igr4 in Dueñas et al, 2014; and mtMutS-5′,CO1 + igr1, 16S-nad2, and igr4 in Morrissey et al, 2022), including the single gene mtMutS presented herein, did not resolve deep nodes within the family. In contrast, there was congruence at all deep nodes in the 75% and 50% conserved element phylogenomic treeswhich were all highly supportedwith only the relationship among M1 specimens and the relationship of group D1 to D2 incongruent between trees.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…These 121 individuals span 11 of 12 previously defined groups, with only G1 absent from our analyses. Previous phylogenies (mtMutS-5′, mtMutS-3′, and 18S in Watling et al, 2022; mtMutS-5′, 16S, and igr4 in Dueñas et al, 2014; and mtMutS-5′,CO1 + igr1, 16S-nad2, and igr4 in Morrissey et al, 2022), including the single gene mtMutS presented herein, did not resolve deep nodes within the family. In contrast, there was congruence at all deep nodes in the 75% and 50% conserved element phylogenomic treeswhich were all highly supportedwith only the relationship among M1 specimens and the relationship of group D1 to D2 incongruent between trees.…”
Section: Discussioncontrasting
confidence: 71%
“…Eknomisis was described in 2011 and, like Keratoisis which was described in 1869, it branches from the internodes . Previous molecular phylogenies, and our mtMutS phylogeny, have recovered Eknomisis nested within the larger Keratoisis D2 group (Dueñas et al, 2014;Morrissey et al, 2022;Watling et al, 2022). In both our 50% and 75% conserved elements phylogenomic inferences, all individuals tentatively identified as Eknomisis from Morrissey et al (2022) and USNM1516861 (identified as Eknomisis due to similarity in polyp morphology and sclerite arrangement to Eknomisis sp., figure S6 in Morrissey et al (2022)) form a distinct clade that is sister to the wider D1&D2 (including H1 representative NIWA106530) group.…”
Section: Clade II 4211 Untangling D1 and D2supporting
confidence: 57%
See 1 more Smart Citation
“…Both phylogenies recovered a deep divergence in keratoisidids, referred to as Clade I and Clade II. This divergence has been reported previously in other conserved element based phylogenomic reconstruction (Morrissey et al 2023a), but was not found in previous phylogenies that used a handful of exclusively mitochondrial markers (mtMuts-5', cox1 + igr1, 16s-nad2, and igr4, (Morrissey et al 2022) or a combination of nuclear and mitochondrial gene regions (mtMuts-5' and 3' and partial 18s, Watling et al 2022) probably due to a lack of phylogenetic signal. The topology of the conserved element phylogeny presented in this study is identical to Morrissey et al's (2023a) conserved element phylogenomic tree, despite the reduced taxon sampling herein (to match the mitochondrial genome sampling).…”
Section: Phylogeny and Mitonuclear Discordancesupporting
confidence: 66%
“…All corals were identified based on morphology observation and molecular analysis of the mitochondrial COI gene ( 49 ) ( Fig. 1 ; Additional file 5: sequences of COI gene).…”
Section: Methodsmentioning
confidence: 99%